The Axiology of Abortion: Should We Hope Pro-Choicers or Pro-Lifers are Right? - Perry Hendricks (Ergo, An Open Access Journal of Philosophy)
The ethics of abortion considers whether abortion is immoral. Pro-choice philosophers think that it is not immoral, while pro-life philosophers think that it is. The axiology of abortion considers whether world would be better if the pro-choice or pro-life position is right. While much attention has been given to the ethics of abortion, there has been no attention given to the axiology of abortion. In this article, I seek to change that. I consider various arguments for thinking our world would be better if the pro-choice position or the pro-life position is correct, ultimately concluding that it would be better if the pro-choice position is right. This is unfortunate, however, since there is no good reason to think the pro-choice position is correct.